2017
DOI: 10.9790/1959-0602060511
|View full text |Cite
|
Sign up to set email alerts
|

Postgraduate nursing students' acquire skills upon applying problem based learning

Abstract: Conclusion:The main conclusion drawn from the current study is that the majority of the postgraduate students were strongly agreed that problem based learning strategy is more effective than traditional learning strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…These results are consistent with recent studies which reported that simulation scenario motivated most of nursing student in intervention group to learn with a valuable learning experience and competent clinical skills [13,24,53,56]. Similarly to our results some researchers found that students were unfamiliar and anxious with problem based scenario but enjoyed with this experience [29,57,58]. On the contrary, other investigators noted that problem based scenario was less stressful and more enjoyable for the majority of nursing students in different courses [30,31,53].…”
Section: Students' Feedbacksupporting
confidence: 93%
See 4 more Smart Citations
“…These results are consistent with recent studies which reported that simulation scenario motivated most of nursing student in intervention group to learn with a valuable learning experience and competent clinical skills [13,24,53,56]. Similarly to our results some researchers found that students were unfamiliar and anxious with problem based scenario but enjoyed with this experience [29,57,58]. On the contrary, other investigators noted that problem based scenario was less stressful and more enjoyable for the majority of nursing students in different courses [30,31,53].…”
Section: Students' Feedbacksupporting
confidence: 93%
“…The current findings supported by Soliman, et al, [29], who adopting problem based leaning education approach in community nursing course for postgraduate nursing students. They noted that students' performance was very good in most achievement items.…”
Section: Students' Achievementsupporting
confidence: 86%
See 3 more Smart Citations